The effects of recurrent episodes of depression on startle responses. (7th October 2013) - Vaidyanathan, Uma; Welo, Evan J.; Malone, Stephen M.; Burwell, Scott J.; Iacono, William G.
Abstract Prior work suggests that major depression is associated with abnormal startle blink responses; however, only chronic or recurrent depression appears to be associated with this effect. The current study tested this hypothesis directly by examining whether recurrent major depression accounted for the anomalous startle seen in major depression using a sample of 515 female twins from the Minnesota Twin Family Study. Blink responses recorded at the age of 20 were examined in relation to number of episodes of depression prospectively assessed from ages 11 to 20. Results showed that only subjects who had experienced multiple episodes of depression showed abnormal startle responses. Subjects who had experienced just one episode of depression in their lifetime did not differ from controls. This lends additional support to the idea that recurrent depression may have a different etiological basis than nonrecurrent depression.